Comportamento de cultivares de soja cultivadas em solo de várzea submetidas a períodos de excesso hídrico - Pazzin, Dalcionei (2012)
Soybean cultivation has increased in regions of low lands, traditionally rice-producing areas, these areas being subject to any conditions of soil flooding. Excess water in the soil for the cultivation of soybean can impair the development, production and seed quality. The objective of this study was to evaluate the effect of flooding in lowland soils, at different times of cultivation on morphological, physiological and productivity of soybean varieties, as well as seed quality. We used five soybean cultivars (IAS-5, BRS Macota, CD 221, BRS 255 RR and BMX Apollo RR) under soil flooding conditions a period of five days at different stages, both in the growing season and in the reproductive tract. The experiment was conducted at the Experimental Station of the Lowlands, from Embrapa Clima Temperado headquartered in the Capão do Leão city, RS. Evaluations were made of the seeds in Didactic Laboratory Seed Analysis, of the Universidade Federal de Pelotas (UFPel). During the crop cycle were evaluated: plant height, main stem diameter, chlorophyll content index, and seed production. The characteristics of the seeds were evaluated for physiological quality, seed weight of 1000 and average size. Statistical analysis for the experiments were performed using analysis of variance to assess the significance of main effects and interactions. The comparison test of Tukey was used to average 5% probability. It was found that productivity is adversely affected by flooding the soil, and there are cultivars that have a lower reduction in output. The weight of thousand seeds is lower when plants suffer stress from excess water in the R5 stage, except the cultivar Apollo BMX RR. Flooding caused a reduction in plant height, and decrease in the chlorophyll content in the leaves. The flooding resulted in variation in the soybean crop cycle, and may postpone or advance depending on the maturity date on which it occurred. Flooding causes negative effect on the physiological quality of seeds, varying according to the time of flooding.